Ritual and Economy: From Mutual Embedding to Non-Profit Festivalisation in Provincial Hungary - Hann, Chris (Ritualas ir ekonomika: nuo abipusės nesuprekintos ekonomikos iki nevyriausybinės festivalizacijos provincinėje Vengrijoje., 2018)
'No human beings, at whatever stage of culture, completely eliminate spiritual preoccupations from their economic concerns' (Malinowski 1935: xx). Drawing on the history and theory of economic anthropology from the pioneering investigations of Bronislaw Malinowski to the work of a postdoctoral research team at the Max Planck Institute for Social Anthropology (Halle/S) between 2009 and 2012, this paper* explores the interface between ritual and the economy in socialist and post-socialist Eastern Europe. The ruptures of early socialism gave way to a re-embedding of the economy that was especially dynamic in the sphere of the household. By contrast, postsocialist disembedding is proving harder to modify. (English)
Keywords: (at)kerėjimas; (dis)enchantment; (po-)socializmas; (post-)socialism; Eastern Europe; Karlas Polanyi; MALINOWSKI, Bronislaw, 1884-1942; POLANYI, Karl, 1886-1964; economic anthropology; ekonomikos nesuprekinimas; ekonominė antropologija; embeddedness; ritual; ritualas; social anthropology; socialism

Markets in West Africa: Karl Polanyi, or what sort of social formation - Saul, Mahir (Market as Place and Space of Economic Exchange: Perspectives from Archaeology and Anthropology, 2018)
Keywords: West Africa; disembeddedness; economic anthropology; economic history; markets